2019
DOI: 10.1093/jas/skz189
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal response to whole body vibration and dietary calcium and phosphorus in growing pigs

Abstract: The quality and strength of the skeleton is regulated by mechanical loading and adequate mineral intake of calcium (Ca) and phosphorus (P). Whole body vibration (WBV) has been shown to elicit adaptive responses in the skeleton, such as increased bone mass and strength. This experiment was designed to determine the effects of WBV and dietary Ca and P on bone microarchitecture and turnover. A total of 26 growing pigs were utilized in a 60-d experiment. Pigs were randomly assigned within group to a 2 × 2 factoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The mechanotransductive forces cause stresses and strains in the extracellular matrix, resulting in confirmation changes at cellular and molecular levels. A wide range of data has shown that whole-body vibration can activate the regeneration of multiple organs [ 3 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanotransductive forces cause stresses and strains in the extracellular matrix, resulting in confirmation changes at cellular and molecular levels. A wide range of data has shown that whole-body vibration can activate the regeneration of multiple organs [ 3 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%